A Preliminary Design of End Effector Stamp Canting for Batik Stamp Automated Production Using Robotic Arm “The Dobot Magician” - Mayusda, Idriwal; Witonohadi, Amal; Dewi Akbari, Annisa (Dinamika Kerajinan dan Batik: Majalah Ilmiah, 2024)
The lack of human resources (HR) hinders batik stamp production in Batik Kembang Mayang studio. At the same time, the high demand for batik must be fulfilled by the studio. This study aims to design an automated batik stamp production using the Robotic Arm “The Dobot Magician” as an alternative to achieving batik demand. The design was initiated by developing and testing a canting stamp tool on the Dobot Magician end effector. The development of canting stamp tool uses Quality Functions Development (QFD) method. The result showed 16 alternative designs of canting stamp tools based on the interpretation of Kembang Mayang Batik studio needs. Then, it is analyzed by Finite Element Analysis methods to get the proposed canting stamp tool design. The selected design of canting stamp tool has 13 attributes of tools specification. It uses polycarbonate material produced by additive manufacturing or 3D printing. Applying in Robotic Arm “Dobot Magician” showed it can produce a stamp batik.